Perspectives on evaluation from curricular contexts - William Schubert (Arizona State University, 2018)
Educational issues in nations throughout the world center on teacher and student evaluation, leading to much consternation. The root of debate stretches to curriculum questions that directly address matters of worth or value. Examining evaluation of education at any level through curricular lenses increases its complexity. First, complexity is approached by focusing on three broad categories that can be framed as questions: What are value considerations in foundations of curriculum? What is worthwhile for subsequent generations? How should we evaluate extant impacts of curricular venues? Second, perspectives on the complexity of evaluation based in curriculum studies are advanced through responses from five orientations to curriculum: Intellectual Traditionalist, Social Behaviorist, Experientialist, Critical Reconstructionist, and Postmodern Global Anti-Imperialist. Each offers a perspective worth considering by those who wish to improve curriculum and its evaluation.